Pięć pytań o postać w konwencji STAND UP COMEDY na podstawie przedstawień Seks, prochy i rock and roll i Czołem wbijając gwoździe w podłogę* - WROCŁAWSKI, BRONISŁAW (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2016)
Five questions on the character within the STAND UP COMEDY convention – based on the following shows: Sex, drugs and rock’n’roll, and Head-hammering nails into the floor The author presents the circumstances related to role construction, which can be formulated in the following questions: who, when, where, why, what for and how. The author utilizes the technique of five questions created by Konstanty Stanisławski to develop his own method designed for the STAND UP COMEDY convention. He analyses various theatre roles, taking into account time and space, as well as the other characters’ motives for action.